A State of Emergency: : Addressing the Suicide Epidemic in Cross Lake, Manitoba - Lang, Sydney (McGill Journal of Global Health, 2017)
“What if staying alive has something to do with witnessing the death in life? What if dying and be- ing borne along by those who love you, is also a way of being alive? How might we come to care for life that is constitutively beside itself, life that could never be fully itself?” -Lisa Stevenson, Life Beside Itself (page 18)